Bypass Seletivo de Nós (BSN): usando algoritmos genéticos para reduzir latência em Smart Grid - Oleinik, Daniel Alexandre (2019)
The increasing consumption of energy from nonrenewable and finite sources is encouraging the advance of development and use of new energy generation options. These options, when incorporated into the current electricity generation and distribution system, should demand new requirements from the communication system, motivating the development of Smart grid. This document proposes a method to improve and optimize the network or grid access, built with optic fiber and mesh topology, through the handling of physical connections in the network and a smart reactive management.